2016
DOI: 10.1021/acs.langmuir.6b02729
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Adhesive Behaviors between Solid Hydrate and Liquid Aqueous Phase Induced by Hydrophobic Silica Nanoparticles

Abstract: This study introduces an "anti-adhesive force" at the interface of solid hydrate and liquid solution phases. The force was induced by the presence of hydrophobic silica nanoparticles or one of the common anti-agglomerants (AAs), sorbitan monolaurate (Span 20), at the interface. The anti-adhesive force, which is defined as the maximum pushing force that does not induce the formation of a capillary bridge between the cyclopentane (CP) hydrate particle and the aqueous solution, was measured using a microbalance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 36 publications
2
33
0
Order By: Relevance
“…They may not only stay at the water–oil interface but can also remain at the solid–liquid interface after hydrate formation. The reduced adhesion force between water droplets and hydrates or between hydrates themselves was also reported by Min et al 19…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…They may not only stay at the water–oil interface but can also remain at the solid–liquid interface after hydrate formation. The reduced adhesion force between water droplets and hydrates or between hydrates themselves was also reported by Min et al 19…”
Section: Discussionsupporting
confidence: 74%
“…In fact, some previous studies are supportive to this hypothesis. Min et al, 19 Cha et al., 20 and Baek et al 21 reported that the silica-NP-laden oil/water interface was less penetrable by hydrate particles and the activated carbon NPs could kinetically prevent hydrate formation by preventing the seeding hydrate penetration into the water phase. The results suggested that the NPs may prevent the coalescence between liquid water droplets and hydrate particles.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the anti-agglomeration performance could be evaluated by the anti-adhesion behavior. Anti-adhesion force is determined as the maximum repulsive force to prevent the formation of the capillary bridge between the aqueous solution drop and the hydrate particle. , Min et al and Lee et al demonstrated that both hydrophobic silica nanoparticles and myristic acid were effective anti-adhesion surface active materials.…”
Section: Introductionmentioning
confidence: 99%
“…Various hydrophobic silicas are of importance from a practical point of view and produced by many companies for a variety of applications. Many problems appearing upon the use of hydrophobic materials are caused by features of their interactions with water, the degree of hydrophobicity, durability of a hydrophobic functional layer, etc. Interaction of water with a solid surface depends not only on the type of functionalization (hydrophobization), but also on the surface topology and confined space effects, as well on the presence of coadsorbates and a dispersion medium type. , On the other hand, water can strongly affect the organization of fumed metal or metalloid oxides (FMO) with respect to the secondary particles such as aggregates of nonporous nanoparticles (NPNP) and agglomerates of aggregates. ,, Additionally, in the systems with hydrophobic particles and water, air bubbles can play an important role in flotation and decrease in the wettability of a particle surface and whole secondary structures with hydrophobized NPNP. , Features of interactions of water with hydrophobic and hydrophilic particles allow one to create “dry” water or the reverse system with hydrophobic cores and hydrophilic shells containing bound water. Note that water bound to hydrophilic components of complex materials (such as polymers, rubbers, and paints filled by pigment particles, etc.) can lead to some negative effects.…”
Section: Introductionmentioning
confidence: 99%